N-Cadherin Regulates the Odontogenic Differentiation of Dental Pulp Stem Cells via β-Catenin Activity - Deng, Zilong; Yan, Wenjuan; Dai, Xingzhu; Chen, Ming; Qu, Qian; Wu, Buling; Zhao, Wanghong (Frontiers in Cell and Developmental Biology, 2021)
Dental pulp stem cell (DPSC) transplantation has shown new prospects in dental pulp regeneration, and is of great significance in the treatment of pulpitis and pulp necrosis. The fate and regenerative potential of stem cells are dependent, to a great extent, on their microenvironment, which is composed of various tissue components, cell populations, and soluble factors. N-cadherin-mediated cell–cell interaction has been implicated as an important factor in controlling the cell-fate commitment of mesenchymal stem cells. In this study, the effect of N-cadherin on odontogenic differentiation of DPSCs and the potential underlying mechanisms, both in vitro and in vivo, was investigated using a cell culture model and a subcutaneous transplantation mouse model. It was found that the expression of N-cadherin was reversely-related to the expression of odontogenic markers (dentin sialophosphoprotein, DSPP, and runt-related transcription factor 2, Runx2) during the differentiation process of DPSCs. Specific shRNA-mediated knockdown of N-cadherin expression in DPSCs significantly increased the expression of DSPP and Runx2, alkaline phosphatase (ALP) activity, and the formation of mineralized nodules. Notably, N-cadherin silencing promoted nucleus translocation and accumulation of β-catenin. Inhibition of β-catenin by a specific inhibitor XAV939, reversed the facilitating effects of N-cadherin downregulation on odontogenic differentiation of DPSCs. In addition, knockdown of N-cadherin promoted the formation of odontoblast-like cells and collagenous matrix in β-tricalcium phosphate / DPSCs composites transplanted into mice. In conclusion, N-cadherin acted as a negative regulator via regulating β-catenin activity during odontogenic differentiation of DPSCs. These data may help to guide DPSC behavior by tuning the N-cadherin-mediated cell–cell interactions, with implications for pulp regeneration.